Strengthening Household Resilience Capacity to mitigate Climate Change for Sustainable Food and Nutritional Security in Benin - S.C. Akpovi; P.V. Vissoh; A.N. Aoudji; N. Fanou; S.D. Vodouhe (European Scientific Journal, ESJ, 2026)
This study analysed the impact of the integrated adaptation programme to mitigate the adverse effects of climate change on agricultural production and food security in Benin to strengthen household resilience capacity for food and nutritional security. The research was carried out in the nine most vulnerable communes to climate change of Benin: Malanville, Ouaké, Savalou, Aplahoué, Sô-Ava, Ouinhi, Matéri, Bopa, and Adjohoun. A combined qualitative and quantitative approach was used for data collection from eighteen villages (nine beneficiary and nine control villages) through group discussion and individual interviews using checklists and structured questionnaires. Using a counterfactual approach, 508 respondents (i.e., 254 beneficiaries and 254 non-beneficiaries) were interviewed. Data analysis comprised descriptive statistics, food and nutrition indicators, comparison tests, and logistic regression. The assessment of food insecurity indicators in the communes identified moderate and severe levels of food insecurity. There were significant differences between beneficiary and non-beneficiary households in terms of both food and nutritional security (p<0.05) and food insecurity (p<0.05). f Female-headed households had a higher probability of experiencing food insecurity (15.15%) compared to male-headed households (8.56%). Binary logistic regression results indicated that age, gender, and education were the determinants of food security status. Furthermore, dietary diversity assessment indicated that the integrated adaptation programme to mitigate the adverse effects of climate change on agricultural production and food security in Benin beneficiary households had more diverse diets compared to non-beneficiary households.